2022
DOI: 10.1002/nop2.1442
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of living with symptomatic atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common arrhythmia. In 2010, more than 33.5 million people worldwide were estimated to be affected and the disease continues to increase in both prevalence and incidence (Chugh et al., 2014). Increased prevalence is due to both improved awareness of AF resulting in systematic diagnosis of AF being made earlier (Kirchhof, Breithardt, et al., 2016) and increases in the life expectancy of the general population (Hindricks et al., 2020).Age is a major risk factor for AF, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Studies also showed that patients avoided planning social activities, their exercise habits were influenced, and their work situations suffered because of disabling symptoms and unpredictable episodes of AF. 28,29 Although European Society of Cardiology guidelines recommend multidisciplinary care for the management of AF, multidisciplinary care is mostly based on a medical and structured approach, based on the "Atrial fibrillation Better Care" pathway (A, avoid stroke; B, better symptom control; and C, cardiovascular risk factors and comorbid condition management). 1 Care of patients with AF would benefit from a more person-centered approach based on the patients' perspectives and needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also showed that patients avoided planning social activities, their exercise habits were influenced, and their work situations suffered because of disabling symptoms and unpredictable episodes of AF. 28,29 Although European Society of Cardiology guidelines recommend multidisciplinary care for the management of AF, multidisciplinary care is mostly based on a medical and structured approach, based on the "Atrial fibrillation Better Care" pathway (A, avoid stroke; B, better symptom control; and C, cardiovascular risk factors and comorbid condition management). 1 Care of patients with AF would benefit from a more person-centered approach based on the patients' perspectives and needs.…”
Section: Discussionmentioning
confidence: 99%
“…In a mixed method study, Stridsman et al 28 found that the consequences of living with AF that most affected HRQoL negatively were impaired physical ability, not being able to perform daily activities, and planning leisure activities. Studies also showed that patients avoided planning social activities, their exercise habits were influenced, and their work situations suffered because of disabling symptoms and unpredictable episodes of AF 28,29 . Although European Society of Cardiology guidelines recommend multidisciplinary care for the management of AF, multidisciplinary care is mostly based on a medical and structured approach, based on the “Atrial fibrillation Better Care” pathway (A, avoid stroke; B, better symptom control; and C, cardiovascular risk factors and comorbid condition management) 1 .…”
Section: Discussionmentioning
confidence: 99%